2015
DOI: 10.3892/or.2015.3983
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ILK inhibits glioma development via upregulation of E-cadherin and downregulation of cyclin D1

Abstract: Integrin-linked kinase (ILK) is a highly conserved serine-threonine protein kinase that interacts with cytoplasmic domains of integrin subunits in tumor tissues. However, the relationship between gliomas and ILK is elusive. The present study aimed to investigate the role of ILK in a human glioma cell line (U251). ILK stable expressing vector, U251ILK-PGFP-V-RS-shRNA, was established and named as U251-si. The empty-PGFP-V-RS-shRNA (U251-N) was employed as the control. Quantitative real-time PCR and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Taken together, these data suggest that mir-218-2 modulates the APC/Cubiquitin–proteasome pathway by targeting CDC27 in glioma cells. Moreover, taking into account that adhesion and cell junction proteins, such as E-cadherin [23, 24], β-catenin [25], focal adhesion kinase (FAK)[26], and vinculin [27] play important roles in cell migration and invasion, we determined their levels of expression by performing Western blotting (Figure 5F–5I). The expression of E-cadherin, in contrast to βcatenin, was decreased in the mir-218-2 group compared to the CGs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data suggest that mir-218-2 modulates the APC/Cubiquitin–proteasome pathway by targeting CDC27 in glioma cells. Moreover, taking into account that adhesion and cell junction proteins, such as E-cadherin [23, 24], β-catenin [25], focal adhesion kinase (FAK)[26], and vinculin [27] play important roles in cell migration and invasion, we determined their levels of expression by performing Western blotting (Figure 5F–5I). The expression of E-cadherin, in contrast to βcatenin, was decreased in the mir-218-2 group compared to the CGs.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, CDC27 has been associated with securin expression and serve as an inverse predictor for the presence of malignant cells and shortened survival in human breast tumor cases [34]. In contrast, cyclin proteins, such as cyclin A [35], cyclin B [36] and cyclin D1 [24, 37, 38], express aberrantly in tumor species. The cyclin/CDK, cyclin A/CDK2, and cyclin D/CDK4 complexes play critical roles in cell cycle control and DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin signalling through ILK has been reported to upregulate the transcriptional repressors SNAIL/SLUG and subsequently suppress E-cadherin transcription 23 25 . Accordingly, our results indicated that the decrease in integrin-β1 led to reduced ILK expression, and subsequently contributed to the upregulation and downregulation of the EMT-related molecules E-cadherin and Snail, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Knock-down of RRM2 also significantly elevated the expression of E-cadherin ( Fig. 3E-3F), a suppressor of glioma development and invasion [43]. Additionally, more apoptotic cells were detected by flow cytometry in the shRRM2-transfected cells than the negative control, accompanied by upregulation of cleaved caspase-3 and downregulation of BCL-2 ( Fig.…”
Section: Discussionmentioning
confidence: 81%